P509 Long-term outcomes of adalimumab in patients with Crohn's disease: Can a doubled dose of adalimumab improve outcomes?. (25th January 2019) - Kanazawa, J; Yokoyama, K; Matsumoto, Y; Kawagishi, K; Mukae, M; Kubota, M; Kobayashi, K; Koizumi, W
Abstract: Background: In anti-TNF agent therapy for inflammatory bowel disease, one agent should be thoroughly used because of immunogenicity issues. We examined the long-term outcomes of treatment with adalimumab (ADA) and effect of a doubled dose of ADA on treatment continuation. Methods: We retrospectively studied 103 patients with Crohn's disease who received ADA from November 2010 through July 2018. The International Organization for the Study of Inflammatory Bowel Diseases (IOIBD) assessment score (0 to 10) was used to evaluate disease activity. Remission was defined as a score of ≤1, and active phase was defined as a score of ≥2. The following variables were studied: (1) the rate of continuing ADA, (2) the outcomes of patients in whom short-term ADA was discontinued, and (3) the proportion of patients in whom the dose of ADA was increased and the treatment response. Results: (1) The rate of continuing ADA was 87% at 1 year, 73% at 2 years, and 50% at 4 years. The most common reason for discontinuing ADA was loss of response (LOR), occurring in 57% of the patients. The rate of continuing ADA was significantly higher in patients whose IOIBD score at the start of treatment was ≤1 than in patients whose IOIBD score was ≥2 (p <0.05). (2) ADA was discontinued within 1 year in 14 patients (14%). The rate of discontinuing ADA decreased from 64% to 36% after coverage of a by doubled dose by insurance. Decreased numbers of patients discontinued treatment because of primary failure, LOR or bowel complications. When demographic characteristics were compared between patients who received short-term treatment and those who received treatment for 4 years or longer ( n = 25), we found that the disease duration before introducing ADA was significantly shorter in patients who received long-term treatment ( p < 0.05). (3) The dose of ADA was increased in 34% of the patients. The reason for a double dose of ADA was worsening of symptoms in 52% and the presence of active residual lesions on imaging studies in 48%. At the time of dose increase, the rate of continuing treatment was 100% at 0.5 year and 73% at 1 year in patients whose IOIBD score was ≤1 as compared with 75.0% at 0.5 year and 62.5% at 1 year in patients whose IOIBD score was ≥2. Conclusions: Low disease activity and shorter disease duration at the time of starting and increasing dose of ADA were associated with good rates of continuing treatment. Increasing the dose of ADA was associated with decreased numbers of patients who discontinued treatment because of LOR or bowel complications. Promptly increasing the dose of ADA on the detection of residual active lesions on imaging studies after the initiation of ADA can be expected to lead to the continuation of treatment and improve outcomes.